2018
DOI: 10.1016/j.applthermaleng.2018.02.106
|View full text |Cite
|
Sign up to set email alerts
|

Miller cycle for improved efficiency, load range and emissions in a heavy-duty engine running under reactivity controlled compression ignition combustion

Abstract: The low temperature, premixed combustion strategies are being investigated in the recent years as a mean to break the NOx-soot trade-off appearing during the diffusive conventional diesel combustion. This approach relies on promoting premixed combustion events with shortened duration, which reduces the heat transfer losses, improves the thermal efficiency, and allows a simultaneous reduction of engine-out NOx and soot emissions. However, since the combustion onset only depends on chemical kinetics, most of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 38 publications
(12 citation statements)
references
References 38 publications
(39 reference statements)
0
9
0
Order By: Relevance
“…In this regard, the advanced combustion modes such as low temperature combustion (LTC) are considered as promising ways to reduce NOX and soot emissions whilst keeping high combustion efficiency [2,3], which could contribute to the simplification of the aftertreatment devices. The use of high exhaust gas recirculation rates (EGR) combined with more premixed conditions than in conventional diesel combustion allow achieving extremely low soot and NOX emissions [4]. Even potentially better emission reductions can be obtained with other strategies such as dual fuel dual mode combustion or Reactivity controlled compression ignition (RCCI) in compression ignition engines in the whole combustion map operating range as recently shown in [5].…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, the advanced combustion modes such as low temperature combustion (LTC) are considered as promising ways to reduce NOX and soot emissions whilst keeping high combustion efficiency [2,3], which could contribute to the simplification of the aftertreatment devices. The use of high exhaust gas recirculation rates (EGR) combined with more premixed conditions than in conventional diesel combustion allow achieving extremely low soot and NOX emissions [4]. Even potentially better emission reductions can be obtained with other strategies such as dual fuel dual mode combustion or Reactivity controlled compression ignition (RCCI) in compression ignition engines in the whole combustion map operating range as recently shown in [5].…”
Section: Introductionmentioning
confidence: 99%
“…17–19 In recent years, however, the main research focus has been on the reduction of NOx emissions from on-road diesel vehicles as the emissions regulation become increasingly stringent. 2024…”
Section: Introductionmentioning
confidence: 99%
“…The basis of this combustion mode has its roots in the work by Inagaki et al [14], where they proposed a dual-fuel premixed compression ignition (PCI) combustion strategy using two fuels with different reactivity. In this concept, the fuels are injected into the cylinder using two separate injection systems, allowing the variation of each fuel independently according to the engine operating conditions [15]. By means of experimental tests, the authors confirmed better combustion controllability than HCCI with low NOx and soot emissions.…”
Section: Introductionmentioning
confidence: 97%